UKM Chemical Engineering students win IEM's 1st Malaysian Chem-E-Car Competition 2004 - Asbi, Ali, Prof. Dr.; Law, Chung Lim, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/